Oral health in preschool children with asthma - MALIN STENSSON, LILL-KARI WENDT, GÖRAN KOCH, GÖRAN OLDAEUS, & DOWEN BIRKHED (IAPD and Blackwell, 2008)
Asthma is one of the most common chronic medical conditions in childhood, and it has steadily increased during the last two decades. The prevalence of asthma in the world displays large variations.